Between-week reliability of motion tracking screening: A preliminary study with youth male football players - Laas, M: M.; Wright, M.; McLaren, S.; Portas, M.; Parkin, G.; Eaves, D. (European Journal of Human Movement, 2021)
We investigated the reliability of fundamental movements in thirteen youth football players (mean age = 16.8 ± 0.6 y). Following a habituation warm-up, players performed three trials of stride-for-distance and bodyweight squats between two weeks. A motion tracking device was used to measure stride distance and squat depth. The weekly mean changes in mean and maximum performance were moderate for the stride (2.8%; 90% confidence interval: 1.1 to 4.5 and 3.6%; 2.1 to 5.2, respectively) and small for the squat (-2.7%; -12.3 to 7.9 and 3.3%; -5.2 to 12.6). ICCs for stride mean and maximum performance were moderate (0.74; 0.43 to 0.90) and high (0.76; 0.46 to 0.90), respectively, and low for the squat (0.22; -0.27 to 0.61 and 0.42; -0.04 to 0.74, respectively). Typical errors for mean and maximum performance were moderate for the stride (2.4%; 1.8 to 3.6 and 2.1%; 1.6 to 3.3, respectively) and large for the squat (15.9%; 11.8 to 25.1 and 13.1%; 9.7 to 20.5, respectively). The motion tracking reliability was encouraging in the stride. This finding warrants further investigation and consideration of the stride test for use in applied practice with a group of youth footballers.